Prevalence of venous thromboembolism after lung surgery in China: a single-centre, prospective cohort study involving patients undergoing lung resections without perioperative venous thromboembolism prophylaxis. (4th October 2018) - Song, Chunfeng; Shargall, Yaron; Li, Hui; Tian, Bo; Chen, Shuo; Miao, Jinbai; Fu, Yili; You, Bin; Hu, Bin
Abstract: OBJECTIVES: Venous thromboembolism (VTE) is a common postoperative complication. Previous studies have shown that the incidence of VTE after major thoracic surgery ranges from 2.3% to 15%. However, there have been no such data from China so far. To evaluate the incidence of postoperative VTE, we conducted a single-centre, prospective cohort study. METHODS: Patients who underwent lung resections between July 2016 and March 2017 were enrolled in this study. None of the patients received any prophylaxis perioperatively. All patients were screened for deep venous thrombosis (DVT) using non-invasive duplex lower-extremity ultrasonography 30 days before surgery and within 30 days after surgery and before discharge. Chest tomography, pulmonary embolism protocol was carried out if patients had one of the following conditions: (i) typical symptoms of pulmonary embolism, (ii) high Caprini score (≥9 points) and (iii) newly diagnosed postoperative DVT. RESULTS: Two hundred and sixty-two patients undergoing lung surgery were enrolled, including 115 benign and 147 malignant disease cases. The procedures included 84 sublobar lung resections, 161 lobectomies, 5 pneumonectomies and 12 mixed procedures. The overall postoperative incidence of VTE was 11.5% (30 of 262). Twenty-four patients were diagnosed with DVT (80.0%) and 6 with DVT + pulmonary embolism (20.0%). None of the patients diagnosed with VTE had obvious symptoms of VTE. The median time for VTE detection was 5 days postoperatively. The incidence of VTE was 7.0% in patients with benign lung diseases and 15.0% in those with malignant lung diseases ( P  < 0.05). Using the Caprini risk assessment model, 63 cases were scored as low risk, 179 as moderate risk and 20 as high risk, and each group had an incidence of postoperative VTE of 0%, 12.3% (22 of 179) and 40.0% (8 of 20), respectively ( P  < 0.05). In patients with lung cancer, 98% were moderate or high risk, and only 3 patients were scored in the low risk category. The incidence of VTE in patients at moderate risk and high risk was 12.0% and 36.8%, respectively, while it was 0 in low-risk patients. CONCLUSIONS: The following conclusions were drawn: (i) the overall incidence of postoperative VTE after lung surgery without VTE prophylaxis is substantial; (ii) lower-extremity ultrasonography was helpful in detecting asymptomatic DVT in symptomatic or high-risk patients; and (iii) VTE prophylaxis should be considered as a mandatory part of perioperative care. Clinical trial registration number: ChiCTR-EOC-17010577.